Investigation into precision engineering design and development of the next-generation brake discs using Al/SiC metal matrix composites - Jake Haley (AIP Publishing LLC, 2021)
Substantially lightweight brake discs with high wear resistance are highly desirable in the automotive industry. This paper presents an investigation of the precision-engineering design and development of automotive brake discs using nonhomogeneous Al/SiC metal-matrix-composite materials. The design and development are based on modeling and analysis following stringent precision-engineering principles, i.e., brake-disc systems that operate repeatably and stably over time as enabled by precision-engineering design. The design and development are further supported by tribological experimental testing and finite-element simulations. The results show the industrial feasibility of the innovative design approach and the application merits of using advanced metal-matrix-composite materials for next-generation automotive and electric vehicles.